Diagnostic accuracy of a loop-mediated isothermal PCR assay for detection of Orientia tsutsugamushi during acute Scrub Typhus infection. - Daniel H Paris; Stuart D Blacksell; Pruksa Nawtaisong; Kemajittra Jenjaroen; Achara Teeraratkul; Wirongrong Chierakul; Vanaporn Wuthiekanun; Pacharee Kantipong; Nicholas P J Day (Public Library of Science (PLoS), 2011)
There is an urgent need to develop rapid and accurate point-of-care (POC) technologies for acute scrub typhus diagnosis in low-resource, primary health care settings to guide clinical therapy.In this study we present the clinical evaluation of loop-mediated isothermal PCR assay (LAMP) in the context of a prospective fever study, including 161 patients from scrub typhus-endemic Chiang Rai, northern Thailand. A robust reference comparator set comprising following 'scrub typhus infection criteria' (STIC) was used: a) positive cell culture isolate and/or b) an admission IgM titer ≥1∶12,800 using the 'gold standard' indirect immunofluorescence assay (IFA) and/or c) a 4-fold rising IFA IgM titer and/or d) a positive result in at least two out of three PCR assays. Compared to the STIC criteria, all PCR assays (including LAMP) demonstrated high specificity ranging from 96-99%, with sensitivities varying from 40% to 56%, similar to the antibody based rapid test, which had a sensitivity of 47% and a specificity of 95%.The diagnostic accuracy of the LAMP assay was similar to realtime and nested conventional PCR assays, but superior to the antibody-based rapid test in the early disease course. The combination of DNA- and antibody-based detection methods increased sensitivity with minimal reduction of specificity, and expanded the timeframe of adequate diagnostic coverage throughout the acute phase of scrub typhus.